83.2k views
5 votes
To find the solution to the equation using factoring, we need to first write it in standard form.

Which of the following choices is equivalent to the equation:
(x - 3)(x + 5) = 10

x^2 + 2x - 5=0
x^2 + 8.2 – 25 = 0
x^2 + 2x – 25 = 0
x^2 + 2x + 5 = 0

1 Answer

4 votes

Answer: the answer is x^2+2x-25

Explanation:

Use distributive property

Multiply the two x’s by each other

Multiply the first x by +5

Multiply the -3 by x

Multiply the -3 by +5

You have x^2+5x-3x-15=10

Move the 10 to the left side and simplify

x^2+2x-25

User Bryan Ward
by
6.5k points